Acquisition of listening behavior, based on selection of figures, in children with contralateral cochlear implants (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Children with hearing loss and cochlear implants have their detection of sounds restored, but understanding what is heard requires learning. This study investigated the learning of hearing based on teaching selection of figures and the relations established with naming in children with recent contralateral cochlear implant. Two children with hearing impairment took part in the study. They were attending early years of elementary school, had received oralism classes and had contralateral cochlear implant activated less than a month before the study. Teaching and tests were conducted by discrete trial and presented by a microcomputer, adopting three sets of stimuli with dictated words and conventional figures. The older cochlear implant was disabled during the sessions. Participants learned how to select figures under control of dictated words, and naming had higher levels than selection.
Keywords: cochlear implant; auditory discrimination; verbal behavior; stimuli control; hearing impairment